Combined effect of arsenic and fluoride at environmentally relevant concentrations in zebrafish (Danio rerio) brain: Alterations in stress marker and apoptotic gene expression. (April 2021) - Mondal, Paritosh; Shaw, Pallab; Dey Bhowmik, Arpan; Bandyopadhyay, Arindam; Sudarshan, Muthammal; Chakraborty, Anindita; Chattopadhyay, Ansuman
Abstract: Arsenic and fluoride are two naturally occurring toxicants to which various organisms including a major part of the human populations are co-exposed to. However, interactions between them inside body are quite complicated and needs proper evaluation. Inconclusive reports regarding their combined effects on brain prompted us to conduct this study where we investigated their individual as well as combined effects on female zebrafish brain at environmentally relevant concentrations (50 μgL −1 arsenic trioxide and 15 mgL − 1 sodium fluoride) after different time intervals (15, 30 and 60 days). Persistent near-basal level of GSH, least increased MDA content and catalase activity portrayed arsenic and fluoride co-exposure as less toxic which was corroborated with far less damage caused in the histoarchitecture of optic tectum region in midbrain. Stress-responsive genes viz., Nrf2 and Hsp70 were overexpressed after individual as well as combined exposures, indicating a common cellular response to combat the formed oxidative stresses. Biphasic response of AChE upon individual exposure confirmed their neurotoxic effects too. Expression profile of p53 (unaltered), Bax (lower or near-basal) and Bcl2 (comparatively higher), along with absence of DNA fragmentation indicated no induction of apoptosis in the co-exposed group. Tissue accumulation of arsenic and fluoride was significantly less in the brain of co-exposed zebrafish when compared to their individual exposures. This preliminary study indicates an antagonistic effect of these two toxicants in zebrafish brain and needs further studies involving oxidative stress independent markers to understand the detailed molecular mechanism. Graphical abstract: Image 1 Highlights: Arsenic and fluoride are the most common hazardous contaminant in the environment. Histological anomalies and alteration of oxidative stress parameters were evident. Stress responsive and apoptotic genes showed less pronounced effects upon co-exposure. DNA ladder was found in both individual treatment, not in combined. Elemental analysis and as3mt gene expression suggests the antagonistic effect.